Culturally Responsive Mathematics Learning Through Classical Malay Literature: Ethnomathematical Perspectives on Gurindam Dua Belas - Asmaul Husna; Ratu Ilma Indra Putri; Zulkardi; Jaya Dwi Putra (Journal of Honai Math, 2025)
Ethnomathematical exploration of classical Malay literature, particularly Gurindam Dua Belas (Gurindam 12), has remained relatively limited despite its considerable potential to support culturally contextualized mathematics learning. This study aimed to examine the mathematical logic structures and set theory concepts embedded in Gurindam 12 by Raja Ali Haji through an ethnomathematical perspective. The study employed a qualitative interpretive design using a literary hermeneutic approach. Primary data were derived from Articles 5 and 6 of Gurindam 12, while secondary data consisted of scholarly publications on ethnomathematics and mathematics education published between 2014 and 2024. Data analysis was conducted through heuristic reading, thematic pattern identification, hermeneutic interpretation, and triangulation with formal mathematical theory. The findings revealed that Article 5 contained inferential structures analogous to mathematical implication logic (p → q), represented through conditional moral relationships, whereas Article 6 reflected classificatory structures parallel to foundational concepts in set theory, including sets, subsets, and membership criteria. The integration of Gurindam 12 into mathematics education offers a culturally responsive ethnomathematical approach that may enhance conceptual understanding, cultural awareness, and positive mathematical dispositions. This study contributes to ethnomathematics literature by demonstrating that classical Malay literature constitutes a meaningful pedagogical resource for bridging indigenous knowledge systems with universal mathematical concepts.